Exploring the Active Constituents of Andrographis paniculata in Protecting the Skin Barrier and the Synergistic Effects with Collagen XVII - Heng Xu; Shiying Lan; Simin Lin; Anjing Wang; Yuanlin Luo; Jing Wang; Zhenzhong Yang (Antioxidants)
Andrographis paniculata is mainly used to treat skin inflammations, wounds, and infections. In this study, Andrographis Herba, the aerial part of the plant, was proven to increase the viability of UVB-damaged HaCat cells and reduce reactive oxygen species levels. The chemical composition of Andrographis Herba extract (AHE) was analyzed using UPLC-Q-TOF-MS, and diterpene lactones were identified as its primary constituents. Then, the fraction of diterpene lactones was prepared and exhibited similar effects to AHE. AHE, its diterpene lactones component, and its representative constituent andrographolide all decreased the expression of IL-1β, IL-6, and CDKN1A. Furthermore, the protective effects of AHE and its active ingredients on UVB-damaged epidermal stem cells were investigated. Notably, the combined treatment with andrographolide and collagen XVII enhanced the viability of UVB-damaged epidermal stem cells, increased the expression of stemness markers integrin β1 and p63, and decreased the expression of the differentiation marker keratin 10. This combination demonstrated significant synergy in maintaining skin homeostasis, which provides evidences for the development of skin-protective products.